BLEEDING MANAGEMENT DURING DELIVERY AND POSTPARTUM PERIOD IN GLANZMANN THROMBASTHENIA: EXPERIENCES FROM TWO CASES - Özden ÖZLÜK (Elsevier, 2021)
Objective: Glanzmann thrombasthenia (GT) is a hereditary bleeding disorder. The platelets lack αIIbβ3integrin and fail to aggregate. Pregnancy can also lead to isoantibody formation when fetal cells with β3integrins pass into the circulation of a mother lacking them; a consequence is neonatal thrombocytopenia and a high risk of mortality. We here present our experience with two GT patients, in which rFVIIa was our choice for bleeding prophylaxis and/or control during delivery and postpartum period. Case report: Case 1: A 28-year-old woman with GT was hospitalized. She was on 38th gestational week (GW). Vaginal delivery was completed with rFVIIa prophylaxis. Postpartum 5th day rFVIIa stopped. The patient discharged with a minimal vaginal bleeding. Postpartum10th day, she developed severe bleeding. GT seemed to be the only related factor. rFVIIa restarted with tranexamic acid and misoprostol. Two apheresis units of platelets were transfused. That time, rFVIIa continued 7 days. Methodology: Case 2: A 26-year-old woman with GT developed hematuria on 30th GW. No urinary system pathology was found. With. rFVIIa treatment, hematuria was ceased. On 39th GW, during labor she developed massive bleeding. As urgent management, 8 random units of platelet and 5 units of packed red blood cell were transfused with local vaginal compress. rFVIIa treatment was initiated. On 10th days of rFIIa with minimal vaginal bleeding the patient was discharged from the hospital. Results: In both of the patients, no major neonatal bleeding problem was experienced. Conclusion: GT patients are at risk for heavy bleeding during labor, deliver or postpartum. Platelet transfusion is simple and easy option for bleeding control. In alloimmunized patients pooled platelet should be used. The use of rFVIIa appears to be safe and relatively effective.